Evaluation of the learning environment designed to develop student mathematics teachers' mathematical modelling competencies. (26th March 2018) - Aydin-Güç, Funda; Baki, Adnan
Abstract: The purpose of this study was to examine the mathematical modelling competencies of student mathematics teachers within a learning environment that was based on a holistic approach to instruction. The participants were student mathematics teachers enrolled in undergraduate programmes at two different universities. In one of the university programmes, the participants took a mathematical modelling course that was taught according to a holistic approach, while the participants at the other university followed the standardized undergraduate programme that did not include a mathematical modelling course. The sub-competencies of mathematical modelling of the student mathematics teachers who participated in the mathematical modelling course were examined using an analytic rubric that was designed according to the holistic approach applied within the context of the study. In order to determine whether the observed changes were related to the experiences of mathematical modelling, these results were compared to the sub-competencies of mathematical modelling of the control group. The findings showed that experience within a learning environment based on mathematical modelling, as well as affective factors, supported the development of modelling competencies. On the other hand, it was observed that certain sub-competencies were difficult to develop; while many sub-competencies were enhanced by the modelling experiences, others were adversely affected. Furthermore, a certain group of sub-competencies was found not to be directly linked to modelling experiences.